2015
DOI: 10.1007/s13197-015-1975-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pin and hammer mill on grinding characteristics, thermal and antioxidant properties of coriander powder

Abstract: In present study, influence of grinding (hammer and pin mills) and moisture content (range: 6.4-13.6 % dry basis) on the quality traits of coriander powder were investigated. These include grinding parameters, colour parameters, specific heat, thermal conductivity, thermal diffusivity, glass transition temperature, essential oil, total phenolic content, total flavonoid content and DPPH scavenging (%) of coriander powder. For coriander seed, the geometric properties such as major, medium, minor dimensions, geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
(18 reference statements)
2
6
0
Order By: Relevance
“…Overall the oil extracted from cryo ground seeds powder was more fresh and pleasant. Similar results were obtained by Barnwal, Singh, Sharma, Choudhary, and Saxena () while comparing ambient and cryogenic ground turmeric powder for its biochemical, antioxidant, and thermal properties.…”
Section: Design Parameters Of Cryogenic Grindersupporting
confidence: 84%
See 1 more Smart Citation
“…Overall the oil extracted from cryo ground seeds powder was more fresh and pleasant. Similar results were obtained by Barnwal, Singh, Sharma, Choudhary, and Saxena () while comparing ambient and cryogenic ground turmeric powder for its biochemical, antioxidant, and thermal properties.…”
Section: Design Parameters Of Cryogenic Grindersupporting
confidence: 84%
“…Overall the oil extracted from cryo ground seeds powder was more fresh and pleasant. Similar results were obtained byBarnwal, Singh, Sharma, Choudhary, and Saxena (2015) while comparing ambient and cryogenic ground turmeric powder for its biochemical, antioxidant, and thermal properties Liu et al (2013). also reported nonsignificant loss in color, flavor, and sensory qualities of different colored pepper on cryogenic grinding.…”
supporting
confidence: 74%
“…Thermal diffusivity data can be used to determine the duration of thermal processes (Mahapatra et al, 2013). The thermal properties of food products can be measured directly, with the use of different devices and techniques such as an analyser KD2 Pro and thermal analysis (Lever et al, 2014;Barnwal et al, 2015;Perussello et al, 2015), and indirectly using mathematical calculations based on the chemical composition (water, protein, fat, carbohydrates, fibre and ash), temperature and structure of the analysed material (Choi, Okos, 1986;Sahin, Sumnu, 2006;Wang et al, 2008;Carson, 2015). Therefore, some of our findings can be used for mathematical modelling.…”
Section: Resultsmentioning
confidence: 99%
“…Also noted was that different treatment could influence the antioxidant properties and phenolic compounds in rice bran and husk (Wanyo, Meeso, & Siriamornpun, 2014). In addition, a previous study suggested that coriander powder in different particle sizes showed different antioxidant activities (Barnwal, Singh, Sharma, Choudhary, & Saxena, 2015). A previous study from our group also observed that the reduction in particle size could effectively increase the availability of wheat antioxidant abilities (Cheng et al., 2006).…”
Section: Introductionmentioning
confidence: 99%